Two Dimensional Simulation of Electromagnetic Waves on Metal Materials Using the FDTD Method. Issue 1 (1st December 2022) - Firdaus, R A; Khoiro, M; Dzulkiflih; Rahayu, V; Mutmainnah
Abstract: It is challenging to picture the physical phenomenon known as electromagnetic wave simulation. The purpose of this work is to model the propagation of electromagnetic waves on a two-dimensional medium. FDTD is a method that is quite relevant to be used in visualizing electromagnetic waves. One can utilise Maxwell's equations to describe discrete electromagnetic waves having TM mode. The simulation is in the form of a Gaussian pulse with the magnetic field H and the electric field E having position and time domains, respectively. The proposed simulation conditions have considered the program's boundary conditions and numerical stability. The differential equation method methodology is used in the FDTD method. The simulation results show that the wave without PML is impeccably reflected, and with PML, the wave is reflected by the material utilized. Materials with high conductivity will make the waves decay and reduce their intensity. This research can be used in the investigation of materials and communication media innovation.